A protective role of Heme-regulated eIF2α kinase in cadmium-induced liver and kidney injuries. (October 2017) - Wang, Lixin; Zhang, Shuping; Wang, Zhe; Xu, Ming; Yuan, Lin; Cui, Jiansheng; Liu, Sijin
Abstract: A number of studies have reported that cadmium (Cd) can incur liver and kidney injuries. The recruitment and activation of leukocytes have been demonstrated to be involved in Cd-induced biological effects. Ironically, activated leukocytes and secreted cytokines are also reported to be required for the later recovery of the damaged tissues. Yet, the mechanisms driving the production of leukocytes have not been fully elucidated. Heme-regulated eIF2α kinase (HRI) is essential for translational regulation and stressed erythropoiesis in iron deficiency. Meanwhile, HRI is important in the maturation and function of macrophages, indicating that HRI might be indispensable for the development and function of other myeloid lineages. Apart from macrophages, whether HRI regulates the production of leukocytes and further affects Cd-induced tissue injuries is still elusive. In this study, we aimed to elucidate the role of HRI in liver and kidney injuries and the associated mechanisms upon Cd exposure. We found that Cd-exposed mice showed impaired production of leukocytes and developed morphological disorders in liver and kidney. Furthermore, Hri null mice exhibited a reduced number of monocytes and neutrophils and compromised cytokine production, relative to wild-type mice. Absence of Hri also exacerbated the impairments of liver and kidney upon Cd treatment. Together, these results highlighted a crucial role of HRI in protecting liver and kidney against Cd-induced injuries through inducing the development of monocytes and neutrophils. Our results further extended the understanding of HRI on the regulation of non-erythroid lineages and might provide new aspects for preventing and treating Cd-induced detrimental effects. Highlights: HRI regulates the development of monocytes and neutrophils and the production of secreted cytokines during cadmium exposure. Regulations on non-erythroid lineages by HRI contribute to the protection from cadmium-induced liver and kidney injuries. HRI deficiency exacerbates cadmium-induced injuries in liver and kidney.